PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI REMAJA TERHADAP PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI DI SMP NEGERI 2 BATANG ANGKOLA TAPANULI SELATAN TAHUN 2017 - SITI KHADIJAH BATUBARA (LP2MTBM MAKARIOZ, 2020)
Based on the results of research on the effect of adolescent reproductive health education on personal hygiene during menstruation at SMP Negeri 2 Batang Angkola Tapanuli Selatan 2017. It can be concluded as follows:There is an effect of adolescent reproductive health education on changes in adolescent knowledge about personal hygiene during menstruation at SMP Negeri 2 Batang Angkola Tapanuli Selatan in 2017, before and after health education was carried out, using the paired t-test so that the average value of knowledge before education was carried out. reproductive health is 0.407 and the average value of knowledge after health education is 0.396 with a probability value (p) = 0.000 where p <0.05.There is an effect of adolescent reproductive health education on changes in adolescent attitudes about personal hygiene during menstruation at SMP Negeri 2 Batang Angkola Tapanuli Selatan in 2017, before and after health education, using the paired t-test so that the average value of attitudes before education is carried out. reproductive health is 0.398 and the average attitude value after health education is 0.325 with a probability value (p) = 0.000 where p <0.05.There is an effect of adolescent reproductive health education on changes in adolescent actions about personal hygiene during menstruation at SMP Negeri 2 Batang Angkola Tapanuli Selatan in 2017, before and after health education, using the paired t-test so that the average value of the action before education is carried out. reproductive health is 0.286 and the average value of action after health education is 0.384 with a probability value (p) = 0.000 where p <0.05.